THE INFLUENCE OF BANK CHARACTERISTICS ON FINANCIAL PERFORMANCE WITH INTELLECTUAL CAPITAL AS INTERVENING VARIABLE - Susanti, Neneng; Sumantri, Muhammad Bayu Aji; Mukhlis, Tanti Irawati; Widajatun, Vincentia Wahju (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to examine the effect of bank characteristics on financial performance using 7 financial proxies on bank characteristics from market concentration of third party funds (HDPK), credit market concentration (HLOA), capital adequacy (CAR), bank liquidity (LDR), bank efficiency. (BOPO), non-performing loans (NPL), leverage (LEV), and Financial Performance with the proxy of Return On Assets (ROA) as the dependent variable and Intellectual Capital as the Intervening variable. Secondary data gathering is the method used for data collecting in this study. This study focuses on Indonesian National Commercial Banks. According to the findings of this study, there is a substantial relationship between Bank Characteristics and Financial Performance, as indicated by a T-statistic of (5.360 > 1.96) and a coefficient of 0.838. With a T-statistic of (4,089 > 1.96), and a coefficient of 0.626, the influence of bank features on intellectual capital is statistically significant. In addition, the Effect of Intellectual Capital on Financial Performance is not statistically significant (0.304 1.96, coefficient = -0.058).